Expedited access to thieno[3, 2-c]quinolin-4(5H)-ones and benzo[h]-1, 6-naphthyridin-5(6H)-ones via a continuous flow photocyclization method. Issue 46 (8th November 2016) - Fang, Y.; Tranmer, G. K.
Abstract : Expedited access to substituted thieno[3, 2- c ]quinolin-4(5 H )-ones and benzo[ h ]-1, 6-naphthyridin-5(6 H )-ones via a continuous flow photocyclization method. Abstract : A single-step continuous flow method has been developed that gives expedited access to complex heterocycles via an intramolecular photochemical cyclization. Herein we report the first examples of the photochemically-induced generation of thieno[3, 2- c ]quinolin-4(5 H )-ones, 16 examples, and benzo[ h ]-1, 6-naphthyridin-5(6 H )-ones, 6 examples. Overall, the continuous flow method provides access to complex heterocycles in two steps from commercially available starting materials in good yields and with greater atom efficiency than traditional batch reactions.